Is Nuclear Security an International Norm? A Constructivist Account of How Nuclear Security Shapes State Behavior - Doan Linh Anh (International Journal of Nuclear Security, 2025)
Since 9/11, nuclear terrorism has been acknowledged to pose a serious threat to global security. In response to this threat, the United Nations Security Council, International Atomic Energy Agency, and nuclear-advanced states such as the US have worked together to develop a global nuclear security regime based on United Nations resolutions, legal conventions, and informal initiatives. However, this regime has been continuously criticized for lacking international standards or, more precisely, an independent nuclear security convention. Although this assertion no doubt holds in comparison with international agreements such as the Treaty on the Non-Proliferation of Nuclear Weapons, nuclear security has made its own significant contribution to the field of global nuclear governance. Notably, it has established itself as an international norm that shapes states’ behavior in the battle against the “evil” threat of nuclear terrorism.
Keywords: nuclear terrorism; non-state actors; nuclear security norms; state behavior; identities; constructivism; nuclear security summits